The Correlation of Platelet Indices; Platelet Count, Mean Platelet Volume (MPV), Platelet Distribution Width (PDW) and Platelet-Large Cell Ratio (P-LCR) with Mortality in Patients Admitted to PICU - Nadeem, Muhammad Tariq; Hassan, Syed Arsalan; Basit, Abdul; Siddiqui, Abdul Wahab; Awan, Aamir Aslam; Ahdi, Saher Gul (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the correlation of platelet indices; platelet count (PC), mean platelet volume (MPV), platelet distribution width (PDW) and platelet large cell ratio (P-LCR) with mortality in patients admitted to PICU.Study Design: Comparative cross-sectional study.Place and Duration of Study: Pediatric Intensive Care Unit (PICU) of CMH Lahore from Jun 2019 to May 2020.Methodology: Cases (mortality group) were the 81 consecutive patients who died in the PICU during the study period and fulfilled inclusion criteria. The control group comprised 81 surviving patients admitted to PICU contemporarily. Both groups' mean values of platelet indices (PC, MPV, PDW and P-LCR) were compared.Results: The mortality rate was 10.42%. Infants were the largest sub-group (45.68%) in the mortality group. Mean platelet counts were significantly low, while mean MPV, PDW and P-LCR were significantly higher in children in the mortality group compared to the control group (p-value